3-(6x-20)=7(x-3)

Simple and best practice solution for 3-(6x-20)=7(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-(6x-20)=7(x-3) equation:


Simplifying
3 + -1(6x + -20) = 7(x + -3)

Reorder the terms:
3 + -1(-20 + 6x) = 7(x + -3)
3 + (-20 * -1 + 6x * -1) = 7(x + -3)
3 + (20 + -6x) = 7(x + -3)

Combine like terms: 3 + 20 = 23
23 + -6x = 7(x + -3)

Reorder the terms:
23 + -6x = 7(-3 + x)
23 + -6x = (-3 * 7 + x * 7)
23 + -6x = (-21 + 7x)

Solving
23 + -6x = -21 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
23 + -6x + -7x = -21 + 7x + -7x

Combine like terms: -6x + -7x = -13x
23 + -13x = -21 + 7x + -7x

Combine like terms: 7x + -7x = 0
23 + -13x = -21 + 0
23 + -13x = -21

Add '-23' to each side of the equation.
23 + -23 + -13x = -21 + -23

Combine like terms: 23 + -23 = 0
0 + -13x = -21 + -23
-13x = -21 + -23

Combine like terms: -21 + -23 = -44
-13x = -44

Divide each side by '-13'.
x = 3.384615385

Simplifying
x = 3.384615385

See similar equations:

| k^3-5k^2-9k+45=0 | | 64z^2-9=0 | | w(w-5)=176 | | n+12=n-8 | | -3(5s-4)-12=-2(9s+5)-2 | | a^2-80=2a | | -3(5s-3)-9=-3(9s+4)-5 | | r^2-30=2+4r | | 9x+1=8x+9 | | -2(4s-5)-10=-3(9s+5)-3 | | m+5(m+1)=7 | | 18u^2-79u-9=0 | | 15-(5x-7)= | | 10x+y=0 | | 2.3n+1=1.3n+7 | | 5(b+7)-2=4(b+3)+5 | | 7(x-2)=5(3x+1)+5 | | 6-2x=6x+10 | | 4(s+3)-1=3(2s+1)+5 | | x^2-308x+23716=0 | | 7a-6=19+2a | | 2x=x+26 | | 4r^2-18r-100=0 | | x+(2x)=12xy*y^2 | | -5(t-3)-(t+4)=10 | | A=2(L+W)(W) | | A=2(L+W) | | 21+(-47)+12+38+(-54)= | | 6y-12y+3= | | X^4-5x^3+11x^2-25x+30=0 | | c=gm | | (2x-3y)(x+2y)=0 |

Equations solver categories